Ideality Factor Mapping of Back‐Contact Perovskite Solar Cells. Issue 9 (20th January 2023) - Rietwyk, Kevin J.; Lin, Xiongfeng; Tan, Boer; Warnakula, Tharindu; Holzhey, Philippe; Zhao, Boya; Deng, Siqi; Surmiak, Maciej A.; Jasieniak, Jacek; Bach, Udo
Abstract: The efficiency of back‐contact perovskite solar cells has steadily increased over the past few years and now exceeds 11%, with interest in these devices shifting from proof‐of‐concept to viable technology. In order to make further improvements in the efficiency of these devices it is necessary to understand the cause of the low fill factor, low open‐circuit voltage ( V OC ), and severe hysteresis. Here a time‐dependent Suns‐ V oc and Suns‐photoluminescence (PL) analysis are performed to monitor the transient ideality factor spatially. Two sets of quasi‐interdigitated back‐contact perovskite solar cells are studied; cells with and without a mesoporous TiO2 layer. Maps of the PL intensity and ideality factor resemble the periodic structure of the back‐contact electrodes and the transient behavior exhibit distinct features such as a temporary variation in the periodicity of the modulation, spatial phase shifting, and phase offsets. It is shown that the presence of the mesoporous layer greatly reduces recombination, increasing the V OC by 0.12 V. Coupled 2D time‐dependent drift‐diffusion simulations allow the experimental results to be modeled, and replicate the key features observed experimentally. They reveal that non‐uniform ion distribution along the transport layer interfaces can drastically alter the PL intensity and ideality factor throughout the device. Abstract : The spatial and temporal evolution in the recombination of back‐contact perovskite solar cells is studied using intensity‐dependent photoluminescence. Maps of the photoluminescence intensity and ideality factor resemble the periodic structure of the back‐contact electrodes and exhibit interesting transient behavior. Adding a mesoporous TiO2 layer drastically reduces recombination and lowers the ideality factor, improving the open‐circuit voltage ( V OC ) by 120 mV.